Efeitos de uma intervenção baseada em mindfulness e autocompaixão em idosas sobre medidas de bem-estar e sintomas de estresse, depressão e ansiedade - Moraes, Allana Almeida (2021)
With life expectancy increasing over the last century, an important direction for research on aging is to explore the factors associated with prosperity at this stage of the life cycle. It is suggested that self-compassion could be one of these factors. This construct has recently emerged, and in addition to being related to a wide range of desirable psychological outcomes, it is considered a particularly important psychological resource for older adults. Thus, the present doctoral thesis was composed of four complementary studies. The first study is a systematic review of the literature, which sought to synthesize available evidence on the potential implications of self-pity in the course of aging. 11 articles were considered eligible, showing self-compassion as a promising skill that can promote psychosocial health, enabling better adjustment to the changes associated with this stage of life. The second and third studies sought to understand the relationship between self-compassion and indicators of well-being and psychopathological symptoms in a sample of 51 elderly women, aged between 60 and 84 years. Pearson correlations and multiple linear regressions were conducted. The results revealed that self-compassion is able to bring benefits to older adults, aiding in the development of healthy aging, and may also benefit the outcomes related to mental health in older adults. The fourth study of the thesis, refers to an exploratory, quantitative and longitudinal study, with assessment of pre- and post-test intervention, which sought to investigate the effects of a program based on self-compassion and mindfulness on measures of well-being - such as, self-compassion, psychological well-being, positive and negative affects, life satisfaction and attitudes towards aging - as well as about symptoms of stress, depression and anxiety, in a sample of 44 Brazilian elderly women, aged between 60 and 84 years. One way, two way ANOVAs and paired t tests were conducted. As a result, there was a significant decrease in the symptoms of stress, anxiety and negative affects and an improvement in the levels of self-compassion, psychological well-being and positive affects in the intervention group. Regarding the battery of instruments, the three studies used the Self-Compassion Scale (EAC), Life Satisfaction Scale (ESV), Positive and Negative Affects Scale (PANAS), Attitudes towards Aging Scale (AAQ Instrument), Psychological Well- Being Scale (EBEP), Geriatric Depression Scale (GDS-15), Geriatric Anxiety Inventory (GAI-BR), Mini Mental State Examination (MMSE), Perceived Stress Scale (EEP), and one more sociodemographic and health data questionnaire. Overall, the results suggest that selfcompassion can represent a valuable psychological resource for older adults, showing that the field of gerontology would benefit from dedicating additional attention to this construct. Research in this area is necessary, as intervention studies, specifically targeting older adults, are still scarce at the national level.